Theoretical Investigation of Solvation Effects on the Tautomerism of Maleic Hydrazide - Meisam Shabanian; Hassan Moghanian; Mohsen Hajibeygi; Azin Mohamadi (E-Journal of Chemistry)
A DFT study is used to calculate structural data of tautomers of maleic hydrazide (MH) in the gas phase and selected solvents such as benzene (non-polar solvent), tetrahydrofuran (polar aprotic solvent) and methanol (protic solvent), dimethyl sulfoxide (polar aprotic solvent) and water (protic solvent) using PCM model. All tautomers are optimized at the B3LYP/6−31++G(d,p). The results show that the tautomer MH2except in methanol is more stable than the other tautomers but in methanol MH5 (Diol) is more stable. In addition, stability of the tautomers in deferent solvents shows interesting results. Variation of dipole moments and NBO charges on atoms in the solvents were studied.